How engagement of a diverse set of stakeholders shaped the design, implementation, and dissemination of a multicenter pragmatic trial of stroke transitional care: The COMPASS study. Issue 1 (5th November 2020) - Gesell, Sabina B.; Coleman, Sylvia W.; Mettam, Laurie H.; Johnson, Anna M.; Sissine, Mysha E.; Duncan, Pamela W.
Abstract: Evidence is limited on how to synthesize and incorporate the views of stakeholders into a multisite pragmatic trial and how much academic teams change study design and protocol in response to stakeholder input. This qualitative study describes how stakeholders contributed to the design, conduct, and dissemination of findings of a multisite pragmatic clinical trial, the COMprehensive Post-Acute Stroke Services (COMPASS) Study. We engaged stakeholders as integral research partners by embedding them in study committees and community resource networks that supported local sites. Data stemmed from formal focus groups and continuous participation in working groups. Guided by Grounded Theory, we extracted themes from focus group and meeting notes. These were discussed as a team and with other stakeholder groups for feasibility. A consensus approach was used. Stakeholder input changed many aspects of the study including: the care model that treated stroke as a chronic condition after hospital discharge, training for hospital-based providers who often lacked awareness of the barriers to recovery that patients face, support for caregivers who were essential for stroke patients' recovery, and for community-based health and social service providers whose services can support recovery yet often go underutilized. Stakeholders brought value to both pragmatic research and health service delivery. Future studies should test the impact of elements of study implementation informed by stakeholders vs those that are not.